2015
DOI: 10.1007/s12035-015-9187-1
|View full text |Cite
|
Sign up to set email alerts
|

High CD133 Expression Is Associated with Worse Prognosis in Patients with Glioblastoma

Abstract: The CD133 antigen has been identified as a putative stem cell marker in gliomas. However, the prognostic significance of CD133 expression in glioblastoma patients remained controversial. A meta-analysis of published data was performed to comprehensively assess the prognostic role of CD133 expression in glioblastoma patients. Publications assessing the prognostic significance of CD133 expression in glioblastoma patients were identified in PubMed, Embase, and Web of Science up to November 2014. The pooled hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 44 publications
(95 reference statements)
2
16
0
2
Order By: Relevance
“…To determine the performance of this online tool, 53 previously published GBM prognostic factors collected as the procedure shown in Figure S1 and then they were evaluated in OSgbm (Table 2, Figure 1) (Sano et al, 1999;Hung and Howng, 2003;Heimberger et al, 2005;Aaberg-Jessen et al, 2009;Shirai et al, 2009;Pu et al, 2011;Cui et al, 2013;De Tayrac et al, 2013;Lee et al, 2013;Rosati et al, 2013;Wang et al, 2013;Wu et al, 2013;Bai et al, 2014;Han et al, 2014;Meng et al, 2014;Olmez et al, 2014;Zupancic et al, 2014;Maris et al, 2015;Moutal et al, 2015;Yan et al, 2015;Zhao et al, 2015;Chaurasia et al, 2016;Nduom et al, 2016;Steponaitis et al, 2016;Steponaitis et al, 2016;Zhang et al, 2016a;Zhang et al, 2016b;Deng et al, 2017;Dong et al, 2017;Ge et al, 2017;Han et al, 2017;Haynes et al, 2017;Huang et al, 2017;Li et al, 2017;Luo and Zhuang, 2017;Ma et al, 2017;Roy et al, 2017;Wu et al, 2017;Zhang et al, 2017;…”
Section: Validation Of Previously Reported Gbm Prognostic Biomarkersmentioning
confidence: 99%
“…To determine the performance of this online tool, 53 previously published GBM prognostic factors collected as the procedure shown in Figure S1 and then they were evaluated in OSgbm (Table 2, Figure 1) (Sano et al, 1999;Hung and Howng, 2003;Heimberger et al, 2005;Aaberg-Jessen et al, 2009;Shirai et al, 2009;Pu et al, 2011;Cui et al, 2013;De Tayrac et al, 2013;Lee et al, 2013;Rosati et al, 2013;Wang et al, 2013;Wu et al, 2013;Bai et al, 2014;Han et al, 2014;Meng et al, 2014;Olmez et al, 2014;Zupancic et al, 2014;Maris et al, 2015;Moutal et al, 2015;Yan et al, 2015;Zhao et al, 2015;Chaurasia et al, 2016;Nduom et al, 2016;Steponaitis et al, 2016;Steponaitis et al, 2016;Zhang et al, 2016a;Zhang et al, 2016b;Deng et al, 2017;Dong et al, 2017;Ge et al, 2017;Han et al, 2017;Haynes et al, 2017;Huang et al, 2017;Li et al, 2017;Luo and Zhuang, 2017;Ma et al, 2017;Roy et al, 2017;Wu et al, 2017;Zhang et al, 2017;…”
Section: Validation Of Previously Reported Gbm Prognostic Biomarkersmentioning
confidence: 99%
“…However, given the limited therapeutic efficacy of TMZ, the importance of MGMT as a standard prognostic marker for GBM is compromised. There are microRNAs and some other genes such as epidermal growth factor receptor (EGFR) or CD133 that show a close correlation with GBM prognosis [ 13 17 ]. However, targeting them has not yet been very successful.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our data revel that CD133 is a key factor contributing to gallbladder carcinoma migration and invasion. Accumulated evidence from clinical and epidemiological studies has shown that high expression of CD133 is associated with poor prognosis in several different types, including brain tumours, colorectal carcinoma, rectal cancer, hepatoma, gastric carcinoma and medulloblastoma [ 27 30 ]. Our data also showed that the expression of CD133 was also significantly increased in gallbladder carcinoma as compared to normal tissues.…”
Section: Discussionmentioning
confidence: 99%